(untitled) (Nigerian Journal of Technology, 2015)
Fonio husk, an agro-waste was incinerated up to a temperature of 6000C and converted into ash. The Fonio Husk Ash (FHA) was used as a partial replacement for Ordinary Portland Cement (OPC) in concrete. The use was expected to reduce environmental pollution and cost on cement. The replacement levels of 0%, 5%, 10%, 15%, 20% and 25% ash were used. The chemical constituents of the FHA as determined from an X-Ray diffraction analyzer included SiO2 (59.45%), Al2O3 (8.19%), K2O (5.20), Fe2O3 (3.51%), CaO (2.70%) and MgO (1.92%). The combined percent of SiO2, Al2O3 and Fe2O3 of 71.14% is above the 70% benchmark for a pozzolana material. The Initial and Final Setting Times of the FHA-Cement paste increased with the increase of FHA up to an optimum of 15% replacement before decreasing. The values were 190 minutes and 205minutes respectively at 5% replacements, and higher than those for plain cement which were 145 and 195 minutes respectively. For 1:2:4 mixes, the FHA Concrete (FHAC) gave compressive strength values in the range of 26.89 N/mm2 for 5% ash and 10.00 N/mm2 for 25% ash at 28 days curing period. The plain concrete had a value of 24.98N/mm2. The trend showed that 10% FHA should not be exceeded for an optimum strength value. The flexural strength values decreased with increase in FHA replacement. The density also followed the trend though marginally. The FHAC will be suitable for mass concreting and use in hot weather. http://dx.doi.org/10.4314/njt.v35i1.5